2008
DOI: 10.1111/j.1523-1739.2008.01034.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Trampling on Populations of Soil Fauna in the McMurdo Dry Valleys, Antarctica

Abstract: Antarctic ecosystems are often considered nearly pristine because levels of anthropogenic disturbance are extremely low there. Nevertheless, over recent decades there has been a rapid increase in the number of people, researchers and tourists, visiting Antarctica. We evaluated, over 10 years, the direct impact of foot traffic on the abundance of soil animals and soil properties in Taylor Valley within the McMurdo Dry Valleys region of Antarctica. We compared soils from minimally disturbed areas with soils from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 37 publications
0
27
1
Order By: Relevance
“…The generally accepted assumption is that disturbance effects on Antarctic soils are very long-lasting, especially in continental environments such as the Victoria Land Dry Valleys and Transantarctic Mountains (Campbell & Claridge 1987;Ayres et al 2008;Hodgson et al 2010). However, our data suggest that some areas of maritime Antarctic soil that have suffered intermediate levels of use could possibly physically recover after a period of as little as twoÁthree years without human presence.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The generally accepted assumption is that disturbance effects on Antarctic soils are very long-lasting, especially in continental environments such as the Victoria Land Dry Valleys and Transantarctic Mountains (Campbell & Claridge 1987;Ayres et al 2008;Hodgson et al 2010). However, our data suggest that some areas of maritime Antarctic soil that have suffered intermediate levels of use could possibly physically recover after a period of as little as twoÁthree years without human presence.…”
Section: Discussioncontrasting
confidence: 48%
“…Several impacts on soil biota have also been identified, the most obvious being reduction in vegetation cover and loss of vegetal biomass around paths (de Leeuw 1994;Pertierra et al 2013). Ayres et al (2008) observed reductions of up to 52 and 76%, respectively, in densities of two species of nematode, Scottnema lindsayae and Eudorylaimus sp., between paths with heavy pedestrian traffic and nearby undisturbed reference areas. Tejedo et al (2009) detected a clear decrease in Collembola abundance with increased pedestrian traffic, and Greenslade et al (2012) similarly noted large reductions in soil collembolan densities in areas on Deception Island subject to a high level of visitation relative to neighbouring undisturbed areas.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Soils around permanent bases can be intensely disrupted by building and heavy equipment use (Kennicutt et al 2010), while environmentally sensitive regions can be impacted by foot traffic (Ayres et al 2008). Trampling has been shown to impact invertebrate species and reduce CO 2 fluxes in Dry Valley soils (Ayres et al 2008), though specific affects on bacterial communities have not been investigated. Bacterial community structures may be altered by trampling due to disturbance of soil crusts, as has been demonstrated in other cold deserts (Kuske et al 2012).…”
Section: Exogenous Factors and Inputsmentioning
confidence: 99%
“…Nematode Scottnema lindsayae exhibited the greatest salinity tolerance of three species found in the Dry Valleys, with drier, more saline, and disturbed sites, being dominated by or solely occupied by S. lindsayae (Wall and Virginia 1999). Ayres et al (2008) compared nematode populations (abundance, ratio of living to dead individuals and dominant species) in tracks used continuously for 10 years during summer months with those used for 2 years. Ayres et al (2008) showed increased nematode mortality, lower abundances and a greater level of physical disturbance to the surface of tracks, which were used at higher intensities and at longer durations, compared with newer tracks and control areas.…”
Section: Disturbance To Fauna and Floramentioning
confidence: 99%